Influences Des Zones Biogéographiques Sur La Diversité Avienne Des Galeries Forestières Au Bénin, Afrique De l’Ouest - Yabi, Francis Biaou; Lougbegnon, Toussaint Olou; Codjia, Jean Timothée Claude (European Scientific Journal, ESJ, 2017)
This study examined the diversity and ecological distribution of riparian bird species across a climatic gradient in Benin. Riparian bird communities were compared among three climatic zones in Benin Republic from December 2012 to November 2015. The diversity and ecological distribution of riparian bird was examined from a census (inventory) of birds in forests galleries across the three climatic zones in Benin by means of a technique of sampling of limited (punctual) type centred on no listening of 20 minutes in a circular plot of 18 m of beam. A total of 140 species richness belonging to 18 orders and 44 families were recorded across climatic zones. The highest (73) species richness were recorded in Guinean zone, followed by Soudanean zone (70) and Soudano – guinean zones, the lowest (68). Similarly, species diversity was highest in Soudanean zone (H’=5.77 bits) and lowest in Soudano – guinean zone (4,28 bits). But we have a significant difference in species diversity between the study climatic zones, but relative abundance of bird are not differed between zones. Further, diverse bird guilds were recorded varying across the climatic gradients indicating the riparian forest conservation importance. Increasing farmland severs more suitable habitats with dire consequences on the survival of disturbance – sensitive bird species. These researches underpin the need for considering integrated bird conservation strategies and are important for planning local ecotourism activities and to protect riparian forest in Benin.